2021
DOI: 10.1038/s41598-021-91276-2
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution metabolomic biomarkers for lung cancer diagnosis and prognosis

Abstract: Lung cancer is the leading cause of human cancer mortality due to the lack of early diagnosis technology. The low-dose computed tomography scan (LDCT) is one of the main techniques to screen cancers. However, LDCT still has a risk of radiation exposure and it is not suitable for the general public. In this study, plasma metabolic profiles of lung cancer were performed using a comprehensive metabolomic method with different liquid chromatography methods coupled with a Q-Exactive high-resolution mass spectromete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Lung tumor cell survival can be inhibited by blocking arachidonic acid metabolism; thus, targeting arachidonic acid action may be beneficial for cancer therapy (22). High plasma levels of palmitic acid were associated with life expectancy for lung cancer patients, which could be used for early lung cancer diagnosis (23)(24)(25). Our results suggest that XHW improves the efficacy of anlotinib by restoring endogenous fatty acid homeostasis.…”
Section: Discussionmentioning
confidence: 72%
“…Lung tumor cell survival can be inhibited by blocking arachidonic acid metabolism; thus, targeting arachidonic acid action may be beneficial for cancer therapy (22). High plasma levels of palmitic acid were associated with life expectancy for lung cancer patients, which could be used for early lung cancer diagnosis (23)(24)(25). Our results suggest that XHW improves the efficacy of anlotinib by restoring endogenous fatty acid homeostasis.…”
Section: Discussionmentioning
confidence: 72%
“…Fatty acids have a key role as structural components of the membrane matrix but can also act as secondary messengers and serve as fuel sources for energy production, and these features are also very relevant under cancer development [59]. Regarding this, very recently Qi, Wu, Chen, Zhang, Zhou, Mao, Li, Li, Chen, Huang, and Huang [18] reported that plasma levels of saturated fatty acids (SFAs), such as dodecanoic acid, were significantly decreased in cancer groups. In turn, altered plasma levels of decanoic acid were reported as a putative new diagnostic biomarker in colorectal cancer [60] and the serum level of octanoic acid were found to predict the efficacy of chemotherapy against the same type of cancer [61].…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…Different studies have shown the potential of such metabolic strategies using human biofluids-including plasma [10], serum [11,12], sweat [13], sputum [14], or urine [10,15,16]. Such metabolic studies incorporating data information from all metabolites found in human biofluids involve fewer variables than genomics and transcriptomics studies [17] but are still complex and hard to analyse [18,19]. To overcome this challenge, researchers focus their attention on subsets of the human metabolites produced by the cells as the volatile organic metabolites (VOMs).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics in a clinical setting supports the identif cation of metabolic biomarkers for cancer detection and surveillance [24]. For exampl high-resolution metabolomics was used to identify the top 5, 10, and 20 metabolites from plasma using HPLC coupled with a Q-Exactive high-resolution mass spectrometer [51 The identification and analysis of high-frequency metabolomic biomarkers with tyrosin on top were reported in a review for breast cancer [51] and a recent study by a Frenc cohort utilized untargeted metabolomics in breast cancer to predict disease outcome [52 Figure 2 depicts the hierarchical interrelationships among the omics.…”
Section: Metabolomics: the "Supra-omic"mentioning
confidence: 99%